Challenges for Serology‐Based Characterization of Foot‐and‐Mouth Disease Outbreaks in Endemic Areas; Identification of Two Separate Lineages of Serotype O FMDV in Uganda in 2011. Issue 5 (11th October 2013) - Namatovu, A.; Belsham, G. J.; Ayebazibwe, C.; Dhikusooka, M. T.; Wekesa, S. N.; Siegismund, H. R.; Muwanika, V. B.; Tjørnehøj, K.
Summary Control of foot‐and‐mouth disease (FMD) in Uganda by ring vaccination largely depends on costly trivalent vaccines, and use of monovalent vaccines could improve the cost effectiveness. This, however, requires application of highly specific diagnostic tests. This study investigated outbreaks of FMD in seven Ugandan districts, during 2011, using the PrioCHECK® FMDV NS ELISA, solid‐phase blocking ELISAs (SPBEs) and virus neutralization tests (VNTs), together with virological analyses for characterization of the responsible viruses. Two hundred and eighteen (218) cattle and 23 goat sera as well as 82 oropharyngeal fluid/epithelial tissue samples were collected. Some 50% of the cattle and 17% of the goat sera were positive by the PrioCHECK® FMDV NS ELISA, while SPBEs identified titres ≥80 for antibodies against serotype O FMD virus (FMDV) in 51% of the anti‐NSP positive cattle sera. However, 35% of the anti‐NSP positive cattle sera had SPBE titres ≥80 against multiple serotypes, primarily against serotypes O, SAT 1 and SAT 3. Comparison of SPBEs and VNTs for the detection of antibodies against serotypes O, SAT 1 and SAT 3 in 72 NSP positive cattle sera showed comparable results against serotype O (P = 0.181), while VNTs detected significantly fewer samples positive for antibodies against SAT 1 and SAT 3 than the SPBEs (P < 0.001). Detection of antibodies against serotype O was consistent with the isolation of serotype O FMDVs from 13 samples. Four of these viruses were sequenced and belonged to two distinct lineages within the East Africa‐2 (EA‐2) topotype, each differing from the currently used vaccine strain (EA‐1 topotype). The relationships of these lineages to other serotype O viruses in the Eastern Africa region are discussed. To enhance the control of FMD in Uganda, there is need to improve the specificity of the SAT‐SPBEs, perform vaccine matching and implement improved regional FMD control.